FACTORS AFFECTING THE PERFORMANCE OF ACCOUNTING INFORMATION SYSTEM IN PT. AGUNG AUTOMALL - Nicky Adi Putranto; Tryas Chasbiandani (INQUISITIVE : International Journal of Economic, 2020)
The purpose of this study is to determine (1) the effect of user involvement in the development of accounting information systems, (2) top management support, (3) personal technical skills, (4) education and training programs, and (5) organizational size on the performance of accounting information systems. This research was conducted on employees of PT. Agung Automall Jakarta. This research uses quantitative methods. This study uses a comparative approach which is a type of research that seeks to know the cause and effect relationship between the dependent variable with the independent variable and test the existing hypothesis. Based on data analysis, it can be concluded that management support, education and training programs, and organizational size have a positive influence on the performance of accounting information systems. While user involvement in the development of the system, and the ability of personal techniques have no significant effect on the performance of accounting information systems.